Competition with List Prices - Marco Haan; Pim Heijnen; Martin Obradovits (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
This paper studies the competitive role of list prices. We argue that such prices are often more salient than actual retail prices, so consumers' purchase decisions may be influenced by them. Two firms compete by setting prices in a homogeneous product market. They first set a list price that serves as an upper bound on their retail price. Then, after having observed each other's list price, they set retail prices. Building on the canonical Varian (1980) model, we assume that some consumers observe no prices, some observe all prices, and some only observe list prices. We show that if the latter partially informed consumers use a simple rule of thumb, the use of list prices leads to lower retail prices on average. This effect is weakened if partially informed consumers are rational.
Keywords: C72; L13; 330; list prices; recommended retail prices; price competition; price dispersion; advertising